Degradation of azo dye with activated peroxygens: when zero-valent iron meets chloride. Issue 49 (15th June 2017) - Wang, Zhaohui; Ai, Luoyan; Huang, Ying; Zhang, Juekai; Li, Sitong; Chen, Jiawei; Yang, Fei
Abstract : Selection of the most appropriate Fe-based peroxygen oxidation technology depends on the dye wastewater constituents and pH. Abstract : Degradation of acid orange 7 (AO7) by Fe 0 -based Advance Oxidation Process (AOPs) with common peroxygens, persulfate (PS), peroxymonosulfate (PMS) and hydrogen peroxide (H2 O2 ), was investigated, in which sulfate radicals (SO4 ˙ − ) and/or hydroxyl radicals (˙OH) are powerful oxidizing species. The effects of Fe 0 dosage, peroxygen concentration, initial pH and the presence of chloride on the degradation of AO7 were examined. The AO7 degradation efficiencies by four systems, including Fe 0, Fe 0 /H2 O2, Fe 0 /PMS and Fe 0 /PS were compared. AO7 degradation rate by Fe 0 activated AOPs in descending order is H2 O2 ≧ PS > PMS. Increasing acidity and iron dosage favored a rapid degradation of AO7. The presence of chloride greatly inhibited dye removal in Fe 0 /H2 O2 and Fe 0 /PS systems, whilst accelerated dye degradation was observed in the Fe 0 /PMS system. In contrast, mineralization of AO7 in the Fe 0 /PMS/Cl − system was minimal, because of formation of lots of refractory chlorinated phenols as identified by GC-MS. These findings are useful for selecting the most appropriate technology for textile wastewater treatment, depending on the wastewater constituents and pH.